Flow Injection Spectrophotometric Determination of Baclofen in Pharmaceutical Formulation Using Prussian Blue Reaction - Fadhil, Ghadah (Al-Nahrain Journal of Science, 2017)
A simple, rapid and sensitive spectrophotometric method for the determination of baclofen in pharmaceutical preparations were developed by combining a spectrophotometric detector with Flow injection analysis. This method based on the oxidation of iron (II) to iron (III) by baclofen and formation of complex between iron (III) and potassium hexacyano ferrate (II) in acidic solution. The absorbance from prussian blue dye is recorded at 700 nm. Chemical and physical parameters of this system were investigated. The linearity of baclofen is ranged from (0.05-25) mmol.L-1 with correlation coefficient r = 0.9972. The limit of detection (S/N=3) was equaled 0.01 mmol.L-1 the L.O.Q was 1.05 mmol.L-1 and a relative standard deviation for 6 replicate determinations of baclofen in 10 mmol.L-1 solution was 1.3 % using 100 µL sample volume. The proposed method was successfully applied to the determination of baclofen in pharmaceutical formulation with recovery 99%. Using paired t-test it was shown that there was no significant difference between the proposed method and official method on that basis the proposed method can be accepted as an alternative analytical method.